Pengembangan Kawasan Rekreasi Pesisir Berbasis Biophilic District dan Eco-Resilient Waterfront - T. Raja Armando; Adi Safyan; Aris Munandar (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The coastal area of Sawang Beach in North Aceh has significant recreational potential but faces challenges such as coastal abrasion, tidal flooding, and spatial degradation caused by development patterns that turn away from the sea. This study aims to formulate strategies for recreational area development through the integration of the Biophilic District concept and Sustainable Eco-Resilient Waterfront. A qualitative descriptive method was employed using a case study approach and literature synthesis. The results indicate that spatial transformation toward a front-yard orientation with biophilic elements enhances human visual and emotional connections to the coastal environment. Resilience strategies are implemented through nature-based solutions, including mangrove belts and adaptive infrastructure, reinforced by placemaking principles rooted in local wisdom, which are projected to increase community activities by up to 45%. In conclusion, the integration of ecosystem protection and cultural preservation is essential for creating a resilient and sustainable coastal recreational area.